3(5+3x)=(6-2x)

Simple and best practice solution for 3(5+3x)=(6-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5+3x)=(6-2x) equation:



3(5+3x)=(6-2x)
We move all terms to the left:
3(5+3x)-((6-2x))=0
We add all the numbers together, and all the variables
3(3x+5)-((-2x+6))=0
We multiply parentheses
9x-((-2x+6))+15=0
We calculate terms in parentheses: -((-2x+6)), so:
(-2x+6)
We get rid of parentheses
-2x+6
Back to the equation:
-(-2x+6)
We get rid of parentheses
9x+2x-6+15=0
We add all the numbers together, and all the variables
11x+9=0
We move all terms containing x to the left, all other terms to the right
11x=-9
x=-9/11
x=-9/11

See similar equations:

| -3r-14+4r=-18+12 | | -4/9x-5/72x+1/8x=56 | | 3=6y-(5+3y) | | X/60=100/x | | 3x-5(x-3)=2+3x+7 | | -20=x-1 | | 15(4x-1)=23 | | -30+z=12 | | -104x=8 | | 14=-56b | | -9-2(-8x-2)=-12 | | x/3+19=23 | | -15=n-2 | | 2/3n-8=1/2n-3 | | x+(x+30)+2x=180 | | 3(n-7)=-63 | | 2/3n-8=1/2-3 | | 2/3n+8=1/2+3 | | 3x+17+5x=7x+10 | | 1/2y-×=-1 | | 15-x÷4=25 | | 15x-10=9×+2 | | ((0.05)(66-x))+0.06x=0.4 | | U10=7+5n-5 | | 31/2x-11=360 | | |2b-9|=2b-6 | | k-2/2=-11 | | 8x+14=4x+2 | | P(x)=-48 | | 0.05(66-x)+0.06x=0.4 | | 12x-18+8=7x | | 12+m=-9 |

Equations solver categories